2018
DOI: 10.1186/s40248-018-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pirfenidone on wound healing in lung transplant patients

Abstract: BackgroundThe drug pirfenidone has been shown to slow the progression and decrease mortality of idiopathic pulmonary fibrosis (IPF). Its exact mechanism is unknown, but it likely inhibits pro-fibrotic cytokine transforming growth factor beta, a known contributor to wound healing. We evaluated whether patients taking pirfenidone until lung transplantation had increased risk of impaired wound healing post-transplant. This information could determine whether pirfenidone should be discontinued prior to listing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Open questions remain regarding the continuation of antifibrotic therapy prior to lung transplantation. Data from small cohort studies suggest that antifibrotic drugs can be safely continued until lung transplantation [151,152] and pirfenidone and nintedanib may also decrease the waiting-list mortality due to their disease progression attenuating effects [153]. Genetic markers such as shorter telomere length can also impact the post-transplantation prognosis by increasing the risk of post-transplant infections such as viral cytomegalovirus and thereby increasing the risks of allograft rejection.…”
Section: Developments In Lung Transplantationmentioning
confidence: 99%
“…Open questions remain regarding the continuation of antifibrotic therapy prior to lung transplantation. Data from small cohort studies suggest that antifibrotic drugs can be safely continued until lung transplantation [151,152] and pirfenidone and nintedanib may also decrease the waiting-list mortality due to their disease progression attenuating effects [153]. Genetic markers such as shorter telomere length can also impact the post-transplantation prognosis by increasing the risk of post-transplant infections such as viral cytomegalovirus and thereby increasing the risks of allograft rejection.…”
Section: Developments In Lung Transplantationmentioning
confidence: 99%
“…The exact mechanism of action of pirfenidone may be from the inhibition of transforming growth factor beta (TGF-b) [23]. A few case reports describe the safety of pirfenidone use as a bridge to lung transplantation [24,25].…”
Section: Studies On Ofev/esbriet Prior To Lung Transplantationmentioning
confidence: 99%
“…Mortensen et al reported the largest retrospective analysis of 18 IPF patients who took pirfenidone prior to lung transplantation [25]. Only one patient developed sternal dehiscence that was more related to a surgical issue.…”
Section: Studies On Ofev/esbriet Prior To Lung Transplantationmentioning
confidence: 99%
“…Sternal wound and airway complications, including anastomotic dehiscence, have been reported in up to 35% of patients after lung transplantation resulting in serious morbidity as well as death. 6 For these reasons, the standard surgical dogma has been to hold antifibrotic agents at the time of listing to prevent such complications. This assumption was primarily based on the mechanistic understanding of pirfenidone's and nintenanib's mechanism of action but not on data-driven clinical science.…”
mentioning
confidence: 99%
“…Only 1 of the patients developed a sternal wound complication, thought not to be related to pirfenidone, and there were no reported airway complications. 6 Cumulatively, such retrospective evidence suggests that pirfenidone may not truly interfere with wound or airway healing post-transplant.…”
mentioning
confidence: 99%